Search for a new bottomonium state decaying to $Υ(1S)π^+π^-$ in pp collisions at $\sqrt{s}$ = 8 TeV - CMS collaboration (2224 authors) (2013)
The results of a search for the bottomonium counterpart, denoted as $X_b$, of the exotic charmonium state X(3872) is presented. The analysis is based on a sample of pp collisions at $\sqrt{s}$ = 8 TeV collected by the CMS experiment at the LHC, corresponding to an integrated luminosity of 20.7 inverse femtobarns. The search looks for the exclusive decay channel $X_b → Υ(1S) π^+ π^-$ followed by $Υ(1S) → μ^+ μ^-$. No evidence for an $X_b$ signal is observed. Upper limits are set at the 95% confidence level on the ratio of the inclusive production cross sections times the branching fractions to $Υ(1S) π^+ π^-$ of the $X_b$ and the $Υ$(2S). The upper limits on the ratio are in the range 0.9-5.4% for $X_b$ masses between 10 and 11 GeV. These are the first upper limits on the production of a possible $X_b$ at a hadron collider.